The Impact of Green Subsidy and Carbon Quota Allocation Modes on Optimal Decisions in A Low-Carbon Supply Chain - Zhang, Yuhao; Yang, Man (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
This study investigates a two-echelon low-carbon supply chain comprising one manufacturer and one retailer, considering distinct green subsidy and carbon quota allocation modes. Four Stackelberg game models are developed, including the GT (grandfathering rule combined with green subsidies based on emission abatement cost), BT (benchmarking rule combined with green subsidies based on emission abatement cost), GA (grandfathering rule combined with green subsidies based on emission abatement amount) and BA (benchmarking rule combined with green subsidies based on emission abatement amount) game models. The joint impacts of carbon-related and subsidy-related parameters on optimal solutions, profitability, environmental benefits, and social welfare of the proposed models are analyzed. A comparative analysis is proposed in terms of optimal equilibrium solutions and model performance. Moreover, numerical simulations are conducted to verify the research results and to seek more managerial insights. The results reveal that a high degree of consumers’ low-carbon preference is conducive to enhancing performance for the entire supply chain. The carbon trading price has different impacts on the chain members’ profits. Moreover, the AB game model is the best option to improve the profitability of the retailer and the social welfare of the entire supply chain, and the manufacturer prefers the GA game model from a profitability perspective. The research findings not only serve to optimize business strategies and performance of enterprises but also provide a theoretical foundation and practical guidance for the effective implementation of low-carbon policies for policymakers.